Pengembangan Potensi Kuliner di Desa Jembrak - Tuwuh Adhistyo W; Rifki A Rahman; Edy Priyanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Tourism villages provide freedom for the community to manage their hometown in accordance with village authenticity. Among the several tourist villages in Semarang Regency, one of them is Jembrak Tourism Village. This village is located in Jembrak Village, Pabelan District, Semarang Regency, Central Java Province. This research aims to examine the involvement of local communities in the development of tourist villages and to formulate a tourism village development model that prioritizes local community participation. The method chosen by the researcher is a type of qualitative research method. The focus in this research is on community participation in the development of Jembrak village. The time needed for this research starts from January to March. The data collection method used in this research is by observing, interviewing, and documenting. The results and discussion obtained in this study include an overview of the Jembrak tourism village and an analysis of local community participation in the development of a tourist village.